M16 Report of the liverpool 'straight to CT' and 'virtual working' lung cancer pathway in its 4th year. (December 2018) - Ledson, MJ; Dunbar, J; Maddock, N; McIver, A; Smyth, C; Walshaw, MJ
Abstract : Streamlining the lung cancer diagnosis pathway is pivotal to improve outcomes and the patient journey. As part of this, in 2014 Liverpool introduced 'straight to CT' where patients with suspicious imaging have a directly arranged (within 72 hours) rapid CT scan, and also the 'virtual assessment' service, where those with scans suggestive of lung cancer are contacted by a lung CNS and the initial clerking and investigation planning is made by telephone. This service is now in its 4th year and we report our experience. As regards 'straight to CT', there has been no increase in CT use for lung cancer (about 400 scans per year), 40% of those enter the virtual assessment pathway, 80% of whom are diagnosed with lung cancer. 21% are referred by the GP to a general chest clinic, the remainder stay in primary care. To date, approximately 1200 patients have been through the 'virtual assessment' service, where surveys have shown that 98% of patients prefer telephone assessment rather than physical clinic attendance, and most wish to be called on the same day as the scan. Patients felt that they had been given both correct and timely information. Primary care feedback is excellent. Lung CNS job satisfaction has improved since skills are now focussed more appropriately. Although the cancer unit diagnoses about 400 cases per year, using the virtual working model means that on average only 7 physical patient clinic attendances per week are necessary to provide the service, thereby greatly reducing resource use, saving 40% of costs overall. Furthermore, the more efficient service easily exceeds the 14 and 62 day cancer targets (99% and 97% respectively). Many lung cancer services are now moving towards 'straight to CT' and virtual working models. Our experience is positive, and we would recommend its adoption.